COMBINATION OF SCIENCE LEARNING USING 2013 AND CAMBRIDGE CURRICULUM IN MIDDLE SCHOOLS - Febri Monica; Bibin Rubini; Rifki Risma Munandar (ATRIUM PENDIDIKAN BIOLOGI, 2022)
The curriculum accommodates students to develop students' understanding, knowledge and skills through learning experiences. The 2013 curriculum implicitly follows the Cambridge Curriculum which emphasizes students' abilities in understanding, knowledge, skills and critical thinking. The purpose of this study was to describe and analyze science learning using a combination of the 2013 curriculum and the Cambridge curriculum at Bosowa Bina Insani Junior High School Bogor. This research is a qualitative research with analytical descriptive method. This research was carried out from January - July 2021 with several informants, namely science teachers, school principals, head level programs, deputy head of student affairs, and students. This research was conducted online and offline and obtained two types of data, namely primary data from interviews and observations, and secondary data from documentation studies. Based on data analysis, science learning using a combination of the 2013 curriculum and the Cambridge curriculum is divided into 3 processes including planning, implementation, and evaluation. Learning planning uses a combination of the 2013 curriculum and the Cambridge curriculum which is carried out at the beginning of each school year with all teachers. The implementation of learning is carried out with a scientific approach with various techniques and learning strategies. Learning evaluation is carried out periodically with formative exams and summative exams with various techniques and assessments. References in making instrument questions use the 2013 curriculum book and cambridge exams that refer to Cambridge University.